2020
DOI: 10.3390/ijms21197227
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Suppresses PM2.5-Induced Neuroinflammation by Regulating Akt Phosphorylation in BV-2 Microglial Cells

Abstract: Air pollution has become one of the most serious issues for human health and has been shown to be particularly concerning for neural and cognitive health. Recent studies suggest that fine particulate matter of less than 2.5 (PM2.5), common in air pollution, can reach the brain, potentially resulting in the development and acceleration of various neurological disorders including Alzheimer’s disease, Parkinson’s disease, and other forms of dementia, but the underlying pathological mechanisms are not clear. Astax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 71 publications
0
30
0
Order By: Relevance
“…Nonetheless, astaxanthin has been shown in human cells to restore SOD2 expression levels following the suppression of its expression by noxious stimuli [ 24 ]. In addition, molecular alterations induced by astaxanthin have been shown to be consistent across cell models of different species, including mice, rats, and humans [ 28 , 29 , 30 ]. Our findings are compatible with existing knowledge and are expected to broaden the clinical indications of astaxanthin in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, astaxanthin has been shown in human cells to restore SOD2 expression levels following the suppression of its expression by noxious stimuli [ 24 ]. In addition, molecular alterations induced by astaxanthin have been shown to be consistent across cell models of different species, including mice, rats, and humans [ 28 , 29 , 30 ]. Our findings are compatible with existing knowledge and are expected to broaden the clinical indications of astaxanthin in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Over recent years, researchers have attempted to prevent and control the cellular and organ damage caused by PM2.5. Some researchers have shown that some natural compounds, and traditional Chinese medicines, can protect the cell and organ damage induced by PM2.5 both in vitro and in vivo, including isovitexin [21], astaxanthin [22], curcumin [23], astragalus [24], codonopsis pilosula [24], ophiopogonin [25], triptolide [26], astragaloside IV [27], resveratrol [28], and lentinan [29]. All of these studies were carried out in vivo; drugs were administered systematically, by either oral or injection routes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ATX microparticles protected macrophages against radiation-induced damage via suppression of transforming growth factor beta [210]. On the other hand, the neuroprotective role of ATX in LPS-activated BV2 cells has been reported in microglia-mediated inflammation following Alzheimer's disease through inhibition of MAPK and NF-κB pathway activation [211,212], as well as in particulate matter-stimulated microglial cells [213]. In addition, ATX inactivated STAT3 transcription factor, which led to inhibition of β-secretase activity with the subsequent prevention of amyloid beta accumulation [214].…”
Section: Astaxanthin 441 In Vitro Studiesmentioning
confidence: 99%